Clinical Profile and Outcomes of Primary PCI in Patients with Acute STEMI - Muhammad Zubair, Abdul Salam, Qamar Zaman, Aslam Latif, Amar Deep, Sara Ahmed (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: Coronary artery disease (CAD) is a significant health concern worldwide, with a notable increase in prevalence in developing nations. Acute ST-segment elevation myocardial infarction (STEMI) represents the most critical manifestation of CAD, often leading to high mortality rates. Primary percutaneous coronary intervention (PCI) is a cornerstone treatment for patients with STEMI, but accessibility and affordability continue to be significant considerations, affecting outcomes. Methodology: A descriptive case series study was conducted to evaluate the clinical outcomes of primary PCI in patients with acute STEMI. The study encompassed a six-month period at a leading cardiology institute. Inclusion criteria were met by patients who received informed consent and underwent reperfusion therapy through established medical approaches. Data on key outcomes like acute stent thrombosis, stroke, atrial fibrillation, and mortality rates were meticulously collected and analyzed. Results: The study comprised 400 individuals with an average age in the late fifties, predominantly male. A fraction of patients experienced acute stent thrombosis and stroke, while a slightly higher percentage developed atrial fibrillation. Notably, mortality was observed in a modest percentage of the patients, with a higher incidence in those above sixty years of age. Conclusion: Primary PCI is an effective treatment for acute STEMI, yet the outcomes, particularly acute stent thrombosis, stroke, atrial fibrillation, and mortality, are considerably high among the elderly population. These findings underscore the need for targeted strategies to improve the prognosis for this age group. Keywords: Coronary artery disease, Primary percutaneous coronary intervention, Acute STEMI, Clinical outcomes, Cardiology, Treatment accessibility.